Trends in Antifungal Susceptibility among Clinical Isolates of Candida spp. Resistant to Antifungals and Natural Products - Padhe1; Kavita Sharma3, Sapna Rai1*, Ashish Saraf2, Sanchali (Journal of Ecobiotechnology, 2011)
A collection of 260 Candida strains isolates recovered from 198 patients from 13 different medical centers in Jabalpur over a period of 5 years.Ã‚Â These were tested for resistance to various antifungals according to the guidelines of NCCLS documents M 38-P by various methods. The isolates which were found to be resistant to synthetic antifungals were selected and subjected to antifungal testing against natural herbs and spices.Amongst all the spices and natural herbs tested garlic was found to the most effective against Candida strains.